DAMPAK PERUBAHAN BUDAYA TERHADAP PENDIDIKAN BUDAYA TERHADAP PENDIDIKAN DI SEKOLAH DASAR KABUPATEN BUTON UTARA - Haliadi; Santi Pujia Ningrum; Fadil Anugra Jaya (JIP: Jurnal Ilmu Pendidikan, 2026)
This research aims to critically analyze the impact of cultural transformation on the learning dynamics in Elementary Schools within North Buton Regency. The background of this study is rooted in concerns over the erosion of local identity due to massive modernization in coastal areas. Utilizing a qualitative sociological approach, this study examines the phenomenon of value shifts from the traditional era of the 1960s to the modern era following the regional expansion in 2007. Data collection was conducted through participant observation and in-depth interviews with educational practitioners in the Kulisusu and West Kulisusu Districts as case study loci. The research findings reveal a significant phenomenon of cultural lag, where advancements in physical infrastructure and access to information technology are not aligned with the preservation of local character values in both the curriculum and daily life. The primary impacts identified are the degradation of students' resilience (daya juang) and a tendency towards instant gratification in learning, as well as the marginalization of local language use in educational interactions at school, which is now dominated by popular slang. Furthermore, this study finds that the local content curriculum has not yet been able to counterbalance the dominance of global culture entering through digital media. In conclusion, cultural transformation in North Buton has created a gap between students' cultural identity and the demands of modern education. This study recommends the need for a local wisdom-based curriculum revitalization integrated with technology, alongside strengthening the teacher's role as a cultural filter within the school environment. Local governments are expected to formulate protection policies for regional languages in formal settings to prevent the extinction of the Kulisusu community's collective identity.